Physiological Characterization and Comparative Transcriptome Analysis of a Slow-Growing Reduced-Thylakoid Mutant of Chinese Cabbage (Brassica campestris ssp. pekinensis) - Huang, Shengnan; Liu, Zhiyong; Li, Danyang; Yao, Runpeng; Hou, Li; Li, Xiang; Feng, Hui (Frontiers in Plant Science, 2016)
Abstract: Mutants are ideal for studying physiological processes. The leaves of Chinese cabbage are a major place for photosynthesis, and the mutation of these leaves may directly affect the rate of plant growth and development, thus influencing the formation of its leafy head. We characterized a slow-growing mutant, which was designated as drm. The drm exhibited slow growth and development at the seedling and heading stages, leading to the production of a tiny, leafy head and chlorophyll-deficient leaves, especially in seedlings. Genetic analysis indicated that the phenotype of drm was controlled by a single recessive nuclear gene. Compared with the wild-type ‘FT’ line, the drm’s chlorophyll content was significantly reduced and its chloroplast structure was abnormal. Moreover, its photosynthetic efficiency and chlorophyll fluorescence parameters were significantly decreased. The changes in leaf color, combined with these altered physiological characters, may influence the growth and development of plant, ultimately resulting in the slow-growing phenotype. To further understand the molecular regulation mechanisms of phenotypic differences between ‘FT’ and drm, comparative transcriptome analyses were performed using RNA-Seq; a total of 338 differentially expressed genes (DEGs) were detected between ‘FT’ and drm. According to GO and KEGG pathway analysis, a number of DEGs involved in chlorophyll degradation and photosynthesis were identified, such as chlorophyllase and ribulose-1,5-bisphosphate carboxylase/oxygenase. In addition, the expression patterns of 12 DEGs, including three chlorophyll degradation- and photosynthesis-related genes and nine randomly-selected genes, were confirmed by qRT-PCR. Numerous single nucleotide polymorphisms were also identified, providing a valuable resource for research and molecular marker-assistant breeding in Chinese cabbage. These results contribute to our understanding of the molecular regulation mechanisms underlying growth and development and lay the foundation for future genetic and functional genomics in Chinese cabbage.